Multiple Fourier Sums on Sets of ψ -Differentiable Functions (Low Smoothness) - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We investigate the behavior of deviations of rectangular partial Fourier sums on sets of ψ-differentiable functions of many variables.